2023
DOI: 10.1080/19490976.2023.2221452
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota in breast cancer development and treatment: The good, the bad, and the useful!

Abstract: Regardless of the global progress in early diagnosis and novel therapeutic regimens, breast carcinoma poses a devastating threat, and the advances are somewhat marred by high mortality rates. Breast cancer risk prediction models based on the known risk factors are extremely useful, but a large number of breast cancers develop in women with no/low known risk. The gut microbiome exerts a profound impact on the host health and physiology and has emerged as a pivotal frontier in breast cancer pathogenesis. Progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Numerous studies have demonstrated the inhibitory impact of butyrate on the proliferation of diverse in vitro cultured tumor cell lines, including colon, esophageal, lung, liver and breast cancer cells, while concurrently promoting tumor cell senescence and apoptosis (65)(66)(67). This effect exhibits a dose-dependent characteristic, with the extent of cellular suppression manifesting progressively with increasing butyrate concentrations (7).…”
Section: Induction Of Tumor Cell Apoptosismentioning
confidence: 99%
“…Numerous studies have demonstrated the inhibitory impact of butyrate on the proliferation of diverse in vitro cultured tumor cell lines, including colon, esophageal, lung, liver and breast cancer cells, while concurrently promoting tumor cell senescence and apoptosis (65)(66)(67). This effect exhibits a dose-dependent characteristic, with the extent of cellular suppression manifesting progressively with increasing butyrate concentrations (7).…”
Section: Induction Of Tumor Cell Apoptosismentioning
confidence: 99%
“…Hence, host gut microbiota cross-talks various physiological processes via modulating immune response, epithelial production, and metabolite production to keep hemostasis. Interestingly, in cancer diseases, human gut microbiota work as immunosuppressive and oncogenic actors based on the abundance of microbiota type and other factors [71]. Furthermore, the presence of gut microbiota has been detected within the tumor microenvironment (TME) and is encountered in most cancer treatments.…”
Section: Gut Microbiota Crosstalk With Icismentioning
confidence: 99%
“…Studies have suggested a potential symbiotic relationship between certain bacterial strains and tumor regression observed in animal models. Nevertheless, there is an unequivocal need for additional research to validate and understand these associations further [28].…”
Section: Bacterial Therapeutics For Tumor Treatment and Immune Modula...mentioning
confidence: 99%